PENGEMBANGAN E-BOOK BERBANTUAN ANYFLIP UNTUK MENINGKATKAN MINAT BELAJAR PADA MATERI MASYARAKAT DI DAERAHKU - Puput Cahyani; Elly Sukmanasa; Didit Ardianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
ABSTRACT E-book is a book in digital format that offers a richer reading experience with multimedia features. However, at SDN Ciluar 02, Bogor Regency, it is not yet varied and not yet digital. Therefore, in the learning process, it is necessary to develop printed teaching materials into digital teaching materials to make them more interesting and varied. The study was aimed at developing and finding out the feasibility of teaching materials assisted by anyflip on the Community in my area material. This study is a Research and Development (R&D) study with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) research method. The data collection technique in this study used an instrument sheet in the form of a questionnaire. Product testing was carried out by media experts, language experts, material experts 1 and material experts 2. The assessment results from media experts were 98%, language experts 96%, material experts 1 96%, and material experts 2 98% which means it is very feasible to be implemented. And based on the limited trial conducted on 22 grade IV students, they obtained a percentage value of 97%, and obtained a percentage value of the student learning interest trial of 93.91%, which means that the e-book assisted by anyflip on the material of the Community in my area is very suitable for use in the learning process and can increase learning interest in students. Keywords: E-book, Anyflip, Learning Interest